Role of BATAN in Preparing Radioisotopes and Radiopharmaceuticals for Cancer Diagnosis and Treatment in Indonesia - mutalib, abdul (Indonesian Journal of Cancer, 2010)
Role of BATAN in Preparing Radioisotopes and Radiopharmaceuticals for Cancer Diagnosis and Treatment in IndonesiaÂ Full text : http://www.scribd.com/doc/43599528/Role-of-BATAN-in-Preparing-Radioisotopes-and-Radiopharmaceuticals-for-Cancer-Diagnosis-and-Treatment-in-Indonesia